Prisoners of the White House : the Isolation of America's Presidents and the Crisis of Leadership. - Walsh, Kenneth T. (Taylor and Francis, 2013)
Prisoners of the White House looks at the isolation experienced by presidents of the United States in the White House, a habitat almost guaranteed to keep America's commander in chief far removed from everyday life. The authors look at how this is emerging as one of the most serious dilemmas facing the American presidency. As presidents have become more isolated, the role of the presidential pollster has grown. Ken Walsh has been given exclusive access to the polls and confidential memos received by presidents over the years, and has interviewed presidential pollsters directly to gain their unique perspective. Prisoners of the White House gets inside the bubble and punctures the mythology surrounding the presidency.